2005
DOI: 10.1111/j.1745-4573.2005.09204.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Gelation Properties of Myofibrillar Protein and Gelatin Combinations

Abstract: Partially purified myofibrillar protein was prepared from post-rigor beef muscle tissue. Gelation properties of myofibrillar protein (6-12%), commercial gelatin (1-12%) and combinations of gelatin and myofibrillar (8-12% protein) were compared. Gels were prepared by combining protein, buffer and 2% NaCl with appropriate volumes of water and heating to 70C at 1.4C/min. Samples were cooled to 4C and gel characteristics were evaluated using texture profile analyses. Gel strength increased as protein concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Calhoun and others (1996) investigated the effects of adding connective tissue collagen to frankfurters and found that hardness, cohesiveness, chewiness, and springiness all decreased. The previously mentioned findings were further confirmed by Brewer and others (2005) who found gel combinations containing both myofibrillar and gelatin protein were much weaker than either the myofibrillar protein or the gelatin gels alone at similar protein concentrations. A similar response was obtained for gumminess and chewiness.…”
Section: Combination Of Myofibrillar and Gelatin Proteinsupporting
confidence: 52%
See 2 more Smart Citations
“…Calhoun and others (1996) investigated the effects of adding connective tissue collagen to frankfurters and found that hardness, cohesiveness, chewiness, and springiness all decreased. The previously mentioned findings were further confirmed by Brewer and others (2005) who found gel combinations containing both myofibrillar and gelatin protein were much weaker than either the myofibrillar protein or the gelatin gels alone at similar protein concentrations. A similar response was obtained for gumminess and chewiness.…”
Section: Combination Of Myofibrillar and Gelatin Proteinsupporting
confidence: 52%
“…Smith and O’Neill (1997) reported that increasing protein concentration from 4% to 8% increased the gel strength of chicken surimi. Using MPs, Brewer and others (2005) also demonstrated the dependence of gel properties on protein concentration as evidenced by increased hardness, chewiness, and gumminess with higher protein concentration. Springiness and cohesiveness increased slightly but inconsistently.…”
Section: Protein Concentrationmentioning
confidence: 93%
See 1 more Smart Citation
“…Decreased in free water content and degradation of fat might be linked to gumminess variation of solid fermentation beef. Brewer, Peterson, Carr, McCusker, and Novakofski () concluded that hardness increase was caused by an increase in the net matrix area occupied by the protein, which increased the potential for interlinks at junctions.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Brewer et al (2005), a combinação de proteínas miofibrilares e de colágeno resulta em maior enfraquecimento do gel formado do que se estas proteínas estivessem isoladas e na mesma concentração.…”
Section: Introductionunclassified